Impact of Covid-19 Pandemic to the Profitability of Villarica Pawnshop Labo Branch, Philippines - Nico Ogarte; Rina Rodelas; Harvin Ong; Sofia Vergara; Angela Padua (The Indonesian Institute of Science and Technology Research, 2023)
Pawnshops are one of the Financial Service Providers (FSP) in the Philippines that are helping to expand underserved and unserved clients' access to financial services. Pawnshops, like the Villarica Labo branch in Camarines Norte, have verified their financial difficulties. Since the outbreak of the pandemic, they have seen a decline in their income. This study aims to know the status of Villarica’s business operations, the factors affecting its profitability, the level of profitability, and the relationship between status and factors to profitability. A descriptive-correlational research design was utilized to describe the variables and identify if there is a significant relationship present. Results have shown that Villarica Labo branch has a very satisfactory performance in its operations despite the pandemic. It also revealed that factors under Government Intervention very highly affects its profitability. Clearly, the pandemic has negatively affected their earnings. Along factors, the customer dealings, company policy, and business competition also have a positive relationship with profitability while government intervention has shown negative relationship. Recommendations mainly focused on transitioning the business into digitization with the inclusion of a business continuity plan during the pandemic lockdowns.